(untitled) (Revista de Ciências Agroveterinárias, 2012)
The study aimed at assessing, by means of an analysis of growth, the behavior of the Carioca Tybatã IAC bean cultivar grown during the rainy season under different levels of phosphorus applied through the soil. The statistical design was based on randomized blocks with five replications. Six phosphate doses were employed: 0, 30, 60, 90, 120 and 150 kg of P2O5 ha-1 in the form of superphosphate triple. The biometric indexes were assessed in order to find the leaf area (cm2 plant-1) and the dry matter weight (g seedling-1). The physiological indexes obtained by means of the functional analysis of growth were: the culture growth rate (g m-2 day-1), the relative growth rate (g g-1 day-1); the net assimilation rate (g m-2 day-1), the leaf area ratio (cm2 g-1) and the specific leaf area (cm2 g-1). The biometric data of the indexes were subjected to analysis of variance and regression study. The increasing levels of phosphorus applied to soil favors the increase of total dry mass and leaf area index of cv. IAC Carioca Tybatã bean. The dry matter has increased constantly throughout the crop cycle and the leaf area index reaches its maximum 97 days after emergence. Phosphorus fertilization also increases the relative growth rate at the beginning of the plant development and the crop growth and reduces the crop cycle.